KOMPARASI HASIL BELAJAR MATEMATIKA MENGGUNAKAN CONTEXTUAL TEACHING AND LEARNING (CTL) DENGAN PEMBELAJARAN KONVENSIONAL SISWA KELAS VII SMP NEGERI 9 MERANGIN - Renita Citra (Mat-Edukasia, 2017)
The purpose of this study was to determine the differences in mathematics learning outcomes using the Contextual Teaching and Learning (CTL) approach with conventional learning. This study uses a quantitative approach with the experimental method. The research design was posttest only control design. The population in this study were all seventh grade students of Merangin 9 Middle School consisting of 3 classes. The sampling technique uses Simple random sampling. Data on the results of mathematics learning using test techniques in the form of problem descriptions. Data analysis techniques used to test hypotheses using independent sample t-test after a test of requirements, namely normal distribution data and homogeneous variance. The results of the analysis of the final test data on the experimental class obtained on average were 70.78, standard deviation 15.45 and in the average control class 61.00 standard deviation was 14.02. Hypothesis test results show that tcount is 2.187 and ttable is 2.017. Because tcount> ttable,then H0 is rejected and Ha accepted, so it can be concluded that there are differences in mathematics learning outcomes approach Contextual Teaching and Learning (CTL) with konvensionl teaching seventh grade students of SMP N 9 Merangin the school year 2015/2016. Keywords: Contextual Teaching and Learning (CTL), Mathematics, Learning Outcomes